Pengaruh Locus Of Control, Pengendalian Internal dan Pengalaman Terhadap Kualitas Laporan Keuangan - Anak Agung Sri Damayanti; Ni Putu Trisna Windika Pratiwi (Hita Akuntansi dan Keuangan, 2022)
This study aims to examine the effect of locus of control, internal control system and work experience on the quality of financial reports at LPDs in Blahbatuh District. The population used is all LPD employees in Blahbatuh District who are registered at LPLPD Gianyar as many as 151 employees. Determination of the sample using purposive sampling in order to obtain 72 employees as a sample. Data were analyzed using multiple linear regression analysis techniques. The results showed that locus of control, internal control system, and work experience, had a positive and significant effect on the quality of LPD financial reports in Blahbatuh District.